A Direct Liquid Fuel Cell with High Power Density Using Reduced Phosphotungstic Acid as Redox Fuel. Issue 1 (22nd March 2021) - Liu, Yiyang; Feng, Ting; Lu, Shanfu; Wang, Haining; Xiang, Yan
Abstract : Direct liquid fuel cells (DLFCs) are proposed to address the problems of high cost and complex storage and transportation of hydrogen in traditional hydrogen–oxygen proton exchange membrane fuel cells. However, present fuels of organic small molecules used in DLFCs are restricted to problems of sluggish electrochemical kinetics and easily poisoning of precious metal catalysts. Herein, we demonstrate reduced phosphotungstic acid as a liquid fuel for DLFCs based on its advantages of high chemical and electrochemical stability, high electrochemical activity on common carbon material electrodes, and low permeability through proton exchange membranes. The application of phosphotungstic acid fuel effectively solves the problems of high cost of anode catalysts and serious fuel permeation loss in traditional DLFCs. A phosphotungstic acid fuel cell achieves a peak power density of 466 mW cm −2 at a cell voltage of 0.42 V and good stability at current densities in the range from 20 to 200 mA cm −2 . Abstract : A direct liquid fuel cell using reduced phosphotungstic acid as redox fuel is constructed, which is expected to both solve the issues of storage and transportation for gas fuel and the high demand of precious metal catalysts for small organic molecule. It achieve an excellent peak power density of 466 mW cm −2 .